Actionable Exomic Secondary Findings in 280 Lebanese Participants - Jalkh, Nadine; Mehawej, Cybel; Chouery, Eliane (Frontiers in Genetics, 2020)
The expanded use of NGS tests in genetic diagnosis enables the massive generation of data related to each individual, among which some findings are of medical value. Over the last three and a half years, 280 unrelated Lebanese patients, presenting a wide spectrum of genetic disorders were referred to our center for genetic evaluation by WES. Molecular diagnosis was established in 56% of the cases, as was previously reported. The current study evaluates secondary findings in these patients in 59 genes, linked to conditions mostly responsive to medical interventions, as per the ACMG guidelines. Our analysis allowed us to detect 19 pathogenic/likely pathogenic variants in 24 individuals from our cohort. Dominant actionable variants were found in 17 individuals representing 6% of the studied population. Genes associated with dominant cardiac diseases were the most frequently mutated: variants were found in 2.1% of our cohort. Genetic predisposition to cancer syndromes was observed in 1.07% of the cases. In parallel to dominant disease alleles, our analysis identified a recessive pathogenic disease allele in 2.5% of the individuals included in this study. Of interest, some variants were detected in different patients from our cohort thus urging the study of their prevalence in our population and the implementation, when needed, of specific genetic testing in the neonatal screening panel. In conclusion, here we report the first study estimating the actionable pathogenic variant load in the Lebanese population. Communicating current findings to the patients will enable them to benefit from a multi-disciplinary approach. Furthermore, tailoring the ACMG guidelines to the population is suggested, especially in highly consanguineous populations where the information related to recessive alleles might be highly beneficial to patients and their families.